Early Ceramics in Anatolia: Implications for the Production and Use of the Earliest Pottery. The Evidence from Boncuklu Höyük. Issue 2 (18th January 2017) - Fletcher, A.; Baird, D.; Spataro, M.; Fairbairn, A.
Abstract : Fragments of possible fired clay found at Boncuklu Höyük, central Turkey, appear to derive from rudimentary vessels, despite the later ninth- and early eighth-millennium cal.bc and thus 'Aceramic' dates for the site. This paper will examine the evidence for such fired clay vessels at Boncuklu and consider their implications as examples of some of the earliest pottery in Anatolia. The discussion will examine contextual evidence for the role of these fragments and consider their relative rarity at the site and the implications for the marked widespread adoption of pottery in southwest Asia c. 7000–6700 cal.bc .